Expression Profile Screening and Bioinformatics Analysis of circRNA, LncRNA, and mRNA in Acute Myeloid Leukemia DrugResistant Cells - Meiling Li; Fuxue Meng; Quanyi Lu (Turkish Journal of Hematology, 2020)
Objective: Acute myeloid leukemia (AML) is a highly heterogeneous hematological malignancy, and drug resistance and relapse are key factors in the failure of leukemia treatment. Studies have increasingly shown that circRNA and LncRNA play important roles in the development of tumors, but their roles remain unclear in the mechanism of AML resistance. Materials and Methods: Resistant AML cell line HL-60/ADM (adriamycin, ADM) was constructed and circRNA, LncRNA, and mRNA expression profiles were screened followed by high-throughput sequencing. Bioinformatics analysis was then carried out, and the circRNA-miRNA ceRNA network was constructed and confirmed using qRT-PCR analysis. Results: A total of 1824 circRNAs, 2414 LncRNAs, and 5346 mRNAs were screened for differentially expressed genes. Enrichment analysis was performed utilizing Gene Ontology and the Kyoto Encyclopedia of Genes and Genomes, which mainly involved protein domain specific binding, transforming growth factor-β (TGF-β) receptor, and cellular metabolism. The mTOR signaling pathway, MAPK signaling pathway, RAP1 signaling pathway, and Akt signaling pathway were closely related to drug resistance. Conclusion: Our study provides a systematic outlook on the potential function of ncRNA in the molecular mechanisms of resistant AML cells. Hsa-circ-0000978 and hsa-circ-0000483 might serve as potential prognostic biomarkers and therapeutic targets of AML resistance.